2020
DOI: 10.1021/acssuschemeng.0c00783
|View full text |Cite
|
Sign up to set email alerts
|

Nanosponge-like Solid Solution of NiMo with a High Hydrogen Evolution Reaction Performance over a Wide Range of Current Densities

Abstract: Owing to unstable electrical energy generation from intermittent solar and wind energy sources, the development of efficient and durable nonnoble electrocatalysts is extremely desirable, in particular, those that can be used over a wide range of current densities for the hydrogen evolution reaction (HER), especially >1 A cm −2 , which is extremely desirable for energy transformation in power systems. Here, a nanosponge-like NiMo solid solution based on a nanoscale Kirkendall effect is fabricated via a one-step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Figure b shows the high-resolution Ni 2p spectra of Ni-MoO 3 for all of the annealed samples. The peaks located at 854.40, 871.49, 856.60, and 875.14 eV in all of the samples can be assigned to Ni 2+ 2p 3/2 , Ni 2+ 2p 1/2 , Ni 3+ 2p 3/2 , and Ni 3+ 2p 1/2 , respectively, , confirming the presence of Ni. For S400, the chemical valence states of Ni are similar to Ni-MoO 3 .…”
Section: Resultsmentioning
confidence: 58%
“…Figure b shows the high-resolution Ni 2p spectra of Ni-MoO 3 for all of the annealed samples. The peaks located at 854.40, 871.49, 856.60, and 875.14 eV in all of the samples can be assigned to Ni 2+ 2p 3/2 , Ni 2+ 2p 1/2 , Ni 3+ 2p 3/2 , and Ni 3+ 2p 1/2 , respectively, , confirming the presence of Ni. For S400, the chemical valence states of Ni are similar to Ni-MoO 3 .…”
Section: Resultsmentioning
confidence: 58%
“…As the Mo precursor content increases to 1.8 and 3.03 wt %, NiO and MoO 2 peaks intensify and the cubic Mo phase is observed. In addition, the Mo peaks are shifted to larger 2θ values, indicating possible Ni–Mo alloy formation or solid solutions of the oxide phases (i.e., Ni 1– x Mo x O y ). We note that the bulk of the electrode is carbon; however, crystalline carbon phases (e.g., graphite) were not observed by XRD, which indicates the carbon is amorphous. X-ray photoelectron spectroscopy (XPS) measurements of NiMo electrodes exhibit peaks for oxidized phases of Ni and Mo at the surface.…”
Section: Resultsmentioning
confidence: 92%
“…The results revealed that the amorphous phase of Ni­(OH) 2 was beneficial to improve the HER activity. The reduced activity of Pt 0.82% NPs-c-Ni­(OH) 2 NSs resulted from the low Pt content and poor conductivity of Ni­(OH) 2 , which led to less active sites for the adsorption of H atoms and the slower charge transfer from the electrode to the catalyst’s surface, while the significantly decreased activity of Pt 5.10% NPs-c-MoO 2 NF was due to the aggregation of Pt nanoparticles and the weak water dissociation kinetics of MoO 2 in an alkaline electrolyte. Furthermore, the Pt 1.07% NPs-c-MoO 2 /a-Ni­(OH) 2 NF electrode can achieve high current densities of 500 and 1000 mA cm –2 at −167 and −256 mV, respectively (inset in Figure a). The Pt mass loading in Pt NPs-c-MoO 2 /a-Ni­(OH) 2 NF can remarkably affect the HER catalytic activity, in which both the products with 0.84 and 1.74% Pt were inferior to that of Pt 1.07% NPs-c-MoO 2 /a-Ni­(OH) 2 NF (Figure S8).…”
Section: Resultsmentioning
confidence: 99%